Understanding the So Called “Anomalous Thermal Strengthening” of Elastic Precursor Decay Tests - Partom, Yehuda (European Journal of Applied Sciences, 2023)
Some time ago a Russian shock physics group performed planar impact tests on thin metal targets (1mm or less) at different temperatures. They were able to observe the elastic precursor wave amplitudes at different target thicknesses and for different target temperatures. They concluded from the test results that the elastic precursor wave decay rate was lower for higher test temperatures, or as they phrased it, dynamic strength increases with temperature. Such a behavior is counter intuitive, as we are used to believe from our experience with quasistatic viscoplastic response, that strength should decrease with temperature. Accordingly, these results of the Russian group were referred to by them as "Anomalous Thermal Strengthening". Our purpose here is to reproduce such test results using a hydrocode. To this end we do the following: 1) we change the way our hydrocode computes dynamic viscoplastic response, from the usually used radial return approach to the more appropriate overstress approach; 2) we compute a planar impact example and reproduce an elastic precursor decay behavior; 3) we show how the quasistatic part of the response can be separated from dynamic part; and 4) we make the quasistatic and the dynamic response parts depend separately on temperature, and in this way we’re able to reproduce the elastic precursor wave increase with temperature, as observed in the above mentioned tests.